Estoque de carbono em diferentes usos da terra e dinâmica das raízes finas em floresta tropical seca - Rosa, Gilberto Quevedo (2018)
In this study, the first stage was developed to quantify the biomass and carbon stocks in the Tropical Dry Forest (FTS) and its alterations after land use change. For this, four land uses were studied: dense caatinga (DC), open caatinga (OC), agriculture (AG) and pasture (PA), in two soil classes (Entisols and Alfisols), in three sites of FTS, Ceará, Brazil. The second stage was developed to analyze the dynamics of the development of fine roots in a DC area in FTSCaatinga. In the first stage, herbaceous stratum, litter and woody species surveys were carried out. The plant material was dried in an oven and weighed, and sub-samples were made to determine the carbon content. The second stage was carried out in Pentecost, starting in July/2015. The existing root system was characterized and the ingrowth cores were implanted. Then, six collections (Nov/2015, Mar/2016, Jul/2016, Nov/2016, Mar/2017 and Jul/2017) were carried out covering two dry and two rainy seasons. Estimates of root length and biomass were developed following the ingrowth core method, in the 0-30 cm layer and in the 0-10, 10-20 and 20-30 cm sub-layers. The roots were separated using two sieves and jets of water. After separation, the roots were oven dried and weighed. To determine the root length, the roots were photographed and analyzed in the Giaroots software. Data were submitted to Mann-Whitney U tests at 5% significance (2 samples) and Kruskal-Wallis H at 5% significance (>2 samples). The total biomass in the areas of CD, CA, AG and PA was 72,90; 38,20; 0,40 and 2,60 Mg ha - 1 , respectively, and the respective total carbon stock was 31,55; 16,67; 0,17 and 1,06 Mg ha-1 . The BRF (<2 mm) in July 2015 was 7,7 ± 5,0 Mg há-1 and the CRF (<2 mm) was 5,0 ± 3,2 km m-2 . At the beginning of the first rainy season the fine roots had already regenerated significantly (ρ<0.05) in relation to their length. However the regeneration of its biomass occurred only at the end of the first rainy season. In the dry season there was a significant reduction (52%) of the biomass only in the deepest layer. Changes in land use from native vegetation areas to agricultural uses result in a major impact on the biomass and carbon stock in the FTS. The production of fine roots occurs mainly in rainy seasons, with a rapid response of development of the root system with occurrence of precipitations.